2005
DOI: 10.1093/ps/84.4.561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary calcium and vitamin D3 on calcium and phosphorus retention in white Pekin ducklings

Abstract: Higher concentrations of Ca in the diet may decrease phytate-phosphorus hydrolysis because of chelation of Ca with the phytin molecule. In experiment 1, drakes were fed 0.74, 0.85, 0.95, or 1.11% Ca (analyzed) from 7 to 18 d of age (6 birds/cage, 8 cages/diet). Intestinal mucosa was collected at 18 d of age from birds fed 0.74 and 1.11% Ca for determination of intestinal phytase activity. In experiment 1, 17 d BW gain and feed consumption exhibited a quadratic response to increasing concentrations of Ca and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…The value for hatchlings (3.1 g/kg) was confirmed for Pekin ducks by Rodehutscord et al (2003), indicating that this remained unchanged over the years. 2 by Rush et al, 2005). In 7 to 17 d old ducks, Rush et al (2005) measured average values for feed/BWG ratio and P utilisation of 1.87 and 46%, respectively.…”
Section: Phosphorus Accretion and P Concentration In Body Weight Gainmentioning
confidence: 96%
See 2 more Smart Citations
“…The value for hatchlings (3.1 g/kg) was confirmed for Pekin ducks by Rodehutscord et al (2003), indicating that this remained unchanged over the years. 2 by Rush et al, 2005). In 7 to 17 d old ducks, Rush et al (2005) measured average values for feed/BWG ratio and P utilisation of 1.87 and 46%, respectively.…”
Section: Phosphorus Accretion and P Concentration In Body Weight Gainmentioning
confidence: 96%
“…The sub-committee on mineral requirements of working group number 2 (Nutrition) of the European Federation of Branches of the WPSA assumed a continuous increase in the P content of body weight (BW) from 3.1 (hatch) to 5.7 g/kg (wk 7) in Pekin ducks, and from Phosphorus use in ducks: M. Rodehutscord 3.1 (hatch) to 6.3 g/kg (wk 12) in Muscovy ducks (WPSA, 1985). In 7 to 17 d old ducks, Rush et al (2005) measured average values for feed/BWG ratio and P utilisation of 1.87 and 46%, respectively. In studies with graded P levels, Pekin ducks achieved a plateau in the P concentration of body weight gain (BWG) of 5.6 g/kg at 2 wk of age, while the value was slightly lower (5.1 g/kg BWG) in 5 wk old ducks .…”
Section: Phosphorus Accretion and P Concentration In Body Weight Gainmentioning
confidence: 98%
See 1 more Smart Citation
“…Rush et al found that white Pekin duckling growth and toe ash weight were maximized with 0.95% and 0.85%, respectively, dietary calcium [18]. This is in contrast to the NRC recommendation of 0.6% dietary calcium and is just one example where published NRC guidelines may not be appropriate for all waterfowl.…”
Section: Basic Nutrition Generalmentioning
confidence: 98%
“…It is evident that the composition of commercial grain mix is different than that of L. multiflorum. The former is usually rich in calcium and phosphate elements, which are very important to the normal growth of ducklings (Rush et al 2005;Xie et al 2009). The MFDR treatment increased the L. multiflorum in the mixed feed during the slow and steady-growth stages of the ducks, which showed positive effects.…”
Section: Effect Of Mfsr Fcgm and Mfdr On The Growth Of Ducksmentioning
confidence: 99%